Total Femur Replacement After Tumor Resection: Limb Salvage Usually Achieved But Complications and Failures are Common. Issue 6 (June 2015) - Sevelda, Florian; Schuh, Reinhard; Hofstaetter, Jochen Gerhard; Schinhan, Martina; Windhager, Reinhard; Funovics, Philipp Theodor
Abstract: Background: Primary bone or soft tissue tumors of the femur sometimes present with severe and extensive bone destruction, leaving few limb‐salvage options other than total femur replacement. However, there are few data available regarding total femur replacement and, in particular, regarding implant failures. Questions/purposes: We asked: (1) What are the revision‐free and overall implant survival rates of conventional total femur replacements in patients treated for sarcoma of the femur or soft tissues? (2) What are the revision‐free and overall implant survival rates of expandable total femur replacements in skeletally immature patients? (3) Using the comprehensive International Society of Limb Salvage failure‐mode classification, what types of complications occur with conventional and expandable total femur replacements? Patients and Methods: Our retrospective, single‐center cohort study was based on data prospectively collected for 50 patients who received a total femur replacement after tumor resection for indications other than carcinoma or metastatic disease. Of the 50 patients, six (12%) were lost to followup before 6 months. Ten of the remaining 44 patients received expandable implants. The mean followup was 57 months (range, 1‐280 months) and 172 months (range, 43‐289 months) for patients who underwent conventional and expandable total femur replacements, respectively. For implant survival, competing risk analyses were used. Results: At 5 years, revision‐free implant survival of conventional total femur replacements was 48% (95% CI, 0.37‐0.73), and overall implant survival was 97% (95% CI, 0.004‐0.20). Five‐year revision‐free implant survival of expandable total femur replacements was 30% (95% CI, 0.47‐1.00) and overall implant survival was 100%. With conventional total femur replacements soft tissue failures occurred in 13 of 34 patients, structural failures in three, infection in six, and local tumor progression in one. No patient had aseptic loosening with conventional total femur replacements, but hip disarticulation occurred in two patients owing to extensive wound‐healing problems and infection. With expandable total femur replacements soft tissue failure, aseptic loosening, and infection occurred in one patient each of 10, and structural failures in three of 10 (two periprosthetic fractures, one loosening of an enhanced tendon anchor). No hip disarticulations were performed. Additionally expandable total femur replacement‐related failures included hip instability in eight of 10 patients, contractures attributable to massive scar tissue in six, and defect of the implant's expansion mechanism in four patients. Conclusions: Although the indications for total femoral resection are rare, we think that total femur replacement is a reasonable treatment option for reconstruction of massive femoral bone defects after tumor resection in adults and skeletally immature patients, and results in limb salvage in most patients. Level of Evidence: Level IV, therapeutic study.